The Impact of Online Service Quality Dimensions on Continuity of Mobile Banking Service Usage: Implications for Customer Loyalty and Bank Reputation - Rahardjo, Irbawanti Pungky; Darma, Emile Satia (Journal of Accounting and Investment, 2025)
Abstract Research Aims: This study aims to empirically examine the impact of the measurement scale for online service quality in the banking sector on the continuity of mobile banking service usage, as well as its potential to enhance customer loyalty and bank reputation. Design/Methodology/Approach: This research employs a quantitative approach using primary data collected from 387 respondents who are customers of Bank Negara Indonesia (BNI). The data is analyzed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) method. Research Findings: The findings suggest that application architecture and user-friendliness do not significantly enhance the continuity of mobile banking service usage. The dimensions of online service quality that do contribute to improving the continuity of mobile banking service usage include application efficiency, reliability, responsiveness, security, and familiarity. Additionally, the continuity of mobile banking service usage is found to have a positive impact on both customer loyalty and bank reputation. Theoretical Contribution/Originality: This study confirms the Theory of Planned Behavior and tests the measurement scale for online service quality in the banking sector, aiming to sustain the existence of banking services in a dynamic environment. Practical/Policy Implications: The results of this study provide valuable insights for the banking sector to enhance the quality of online services, particularly in a rapidly changing environment.